2005
DOI: 10.1016/j.amjcard.2005.07.025
|View full text |Cite
|
Sign up to set email alerts
|

European Experience on the Practical Use of Levosimendan in Patients with Acute Heart Failure Syndromes

Abstract: The novel calcium sensitizer and ATP-dependent potassium channel opener levosimendan has been introduced for routine use in several European countries. Recent reports on clinical experience confirm the positive hemodynamic results and beneficial clinical effects described in the initial dose-finding and randomized comparative therapeutic trials in patients with severe low-output heart failure. In addition, studies in small series of patients with cardiogenic shock after myocardial infarction and/or surgical in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0
2

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 30 publications
2
8
0
2
Order By: Relevance
“…Previous studies have demonstrated the beneficial clinical and hemodynamic effects of levosimendan in patients with decompensated HF [6][7][8][9][10][11][12][13][14] and with left ventricular dysfunction after ST segment elevation myocardial infarction, [15][16][17] so that in recent European Society of Cardiology guidelines it has been recommended with a class IIa, level of evidence B indication. 18 The effective role of levosimendan in the treatment of decompensated congestive HF has not been completely clarified, however, especially in relation to the exact time in which to start using this drug in the pharmacologic sequence of a patient's treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated the beneficial clinical and hemodynamic effects of levosimendan in patients with decompensated HF [6][7][8][9][10][11][12][13][14] and with left ventricular dysfunction after ST segment elevation myocardial infarction, [15][16][17] so that in recent European Society of Cardiology guidelines it has been recommended with a class IIa, level of evidence B indication. 18 The effective role of levosimendan in the treatment of decompensated congestive HF has not been completely clarified, however, especially in relation to the exact time in which to start using this drug in the pharmacologic sequence of a patient's treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Levosimendan reduces elevated pulmonary capillary wedge pressure and increases cardiac output 10 The beneficial haemodynamic effects of levosimendan, unlike those of dobutamine, are not attenuated by the concomitant use of β‐blockers,10 which makes the drug specifically suitable for use in chronic HF. Levosimendan offers renal protection and increases peripheral organ perfusion 30 Previous studies in severe HF patients such as REVIVE‐I and II revealed a higher rate of clinical improvement in levosimendan‐treated patients than in placebo patients 31.…”
Section: Discussionmentioning
confidence: 99%
“…After 180 days, there was no difference in all-cause mortality [12]. The recommended dose is 0.05-0.2 mg/kg/min, but levosimendan is not recommended in systolic blood pressures <90 mmHg [19]. At 5 days after randomization patients in the levosimendan group had better symptoms, lower serum B-type natriuretic peptide levels and shorter length of hospital stay compared with placebo.…”
Section: Calcium Sensitizersmentioning
confidence: 98%